2014
DOI: 10.1128/iai.00055-14
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Long-Lasting Hydrosalpinx in A/J Mice Correlates with Rapid but Transient Chlamydial Ascension and Neutrophil Recruitment in the Oviduct following Intravaginal Inoculation with Chlamydia muridarum

Abstract: dLower genital tract infection with Chlamydia trachomatis and C. muridarum can induce long-lasting hydrosalpinx in the upper genital tract of women and female mice, respectively. However, A/J mice were highly resistant to induction of long-lasting hydrosalpinx by C. muridarum. We further compared host inflammatory responses and chlamydial infection courses between the hydrosalpinx-resistant A/J mice and CBA/J mice known to be susceptible to hydrosalpinx induction. Both mouse strains developed robust pyosalpinx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Thus, the progesterone may contribute to chlamydial induction of the uterine horn/glandular duct dilation and hydrosalpinx by increasing mouse susceptibility to C. muridarum infection in the upper genital tract. This assumption is supported by the observation that live infection in the upper genital tract is required for C. muridarum induction of pathologies in the upper genital tract (9,15). Although there is an association of the use of the progesterone receptor modulators (as contraceptives) with inactive endometrium cyst-dilated glands in women (44), there has been no direct evidence of the induction of uterine horn/glandular duct dilation in mice by progesterone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the progesterone may contribute to chlamydial induction of the uterine horn/glandular duct dilation and hydrosalpinx by increasing mouse susceptibility to C. muridarum infection in the upper genital tract. This assumption is supported by the observation that live infection in the upper genital tract is required for C. muridarum induction of pathologies in the upper genital tract (9,15). Although there is an association of the use of the progesterone receptor modulators (as contraceptives) with inactive endometrium cyst-dilated glands in women (44), there has been no direct evidence of the induction of uterine horn/glandular duct dilation in mice by progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…An extensively investigated pathology is the long-lasting hydrosalpinx that can be induced by Chlamydia trachomatis infection in women (3,4) and Chlamydia muridarum infection in female mice (5)(6)(7)(8)(9). Thus, the C. muridarum mouse genital tract infection model has been extensively used to investigate the mechanisms of C. trachomatis-induced hydrosalpinx in women.…”
mentioning
confidence: 99%
“…This is because a single inoculation of C. muridarum organisms in the mouse lower genital tract can cause hydrosalpinx and infertility (7)(8)(9), closely mimicking the tubal adhesion, hydrosalpinx, and infertility observed in women urogenitally infected with C. trachomatis (10)(11)(12). Although C. muridarum is not a natural sexually transmitted agent of mice, chlamydiologists have used this model not only to identify both chlamydial (13)(14)(15)(16)(17) and host (1,5,(18)(19)(20)(21)(22)(23)(24) pathogenic determinants but also to define the roles of ascending infection and tubal inflammation in chlamydial induction of hydrosalpinx (9,16,25,26). Nevertheless, questions such as how a self-limited infection with C. muridarum in the mouse genital tract can trigger tubal fibrosis or hydrosalpinx that lasts long after the tubal infection is resolved (9,25) remain unanswered.…”
mentioning
confidence: 99%
“…Mutant CPAF, however, failed to inhibit antigen presentation, showing similar levels of IL-2 production even with high doses of mutant CPAF (100 μg/mL) ( Figure 1A column 9). To our surprise, when OT1 was replaced with OT2 to perform the same experiment, we found that even wt CPAF failed to inhibit any antigen presentation activity, showing that IL-2 production was similar between groups from OT1 with pre-incubation of wt CPAF or without preincubation of wt CPAF ( Figure 1A, panel b, columns [5][6][7][8]. This experiment demonstrates that CPAF can inhibit OT2-but not OT1-mediated antigen presentation and that inhibition is dependent upon CPAF enzymatic activity.…”
Section: Cpaf Inhibits Ot2-but Not Ot1-mediated Antigen Presentationmentioning
confidence: 98%
“…Recently, it was hypothesized that both adequate ascension to and induction of the appropriate inflammatory response in the upper genital tract is necessary for hydrosalpinx development [6][7][8][9]. To overcome the host immunity barriers, and establish the successful infection, chlamydia may utilize virulence factors as previously proposed [10].…”
Section: Introductionmentioning
confidence: 97%